VEGFR-3 Expression in Oral Lichen Planus - Saravi, Zahra Zolfaghari (Asian Pac J Cancer Prev, 2017)
BACKGROUND AND OBJECTIVE: Given the postulated the role of inflammation and possible contribution of lymphangiogenesis in oral lichen planus, this study aimed to assess any associated presence of VEGFR-3. MATERIAL AND METHODS: This cross-sectional study was performed on 52 formalin fixed and paraffin embedded blocks of oral lichen planus (pathological diagnosis based on Modified WHO criteria), comprising 25 of erosive and 27 of reticular type, along with 60 samples of normal mucosa (with minimal inflammation from clinical and histopathological aspects) obtained at crown lengthening surgery. Four micron sections were cut from paraffin blocks and stained with H and E for confirmation of diagnosis and by immunohistochemistry with primary antibodies against VEGFR-3. Negative controls were provided by omission of primary antibody and placenta was considered as a positive control. Data were analyzed by Chi-square, Mann-Whitney and Kruskal-wallis tests and P <0.05 was considered statistically significant. FINDINGS: VEGFR-3 expression was apparent in 61.5% of lichen planus specimens and 5% of those from normal mucosa (p<0.001). Also, the average number of stained vessels was significantly higher in oral lichen planus than in normal mucosa (p<0.001). VEGFR-3 expression in oral lichen planus (p=0.262) and the average number of stained vessels (p=0.092) demonstrated no significant difference according to the type. CONCLUSION: It appears that VEGFR-3 expression might be involved in the pathogenesis of the oral lichen planus through increasing lymphatic vessels and lymphangiogenesis.